Potential Sauna Bath and Eucalyptus Aromatherapy on Reducing Fatigue and Lactic Acid in Corona Virus Disease (COVID-19) Nurses - Wulandari, Dinar Jantik; Sudirman, Sudirman; Santoso, Bedjo (Alta Dharma Publisher, 2023)
Background: A high workload requires a lot of energy, so upgrading lactic acid raises fatigue. Complementary therapy was done to reduce fatigue and rate lactic acid. Objective: This study aims to analyze the potencial action combination bathe a sauna and aromatherapy of eucalyptus, to manage the fatigue reduction and improve lactic acid level among nurses with covid-19. Method: A quasi-experiment, pre-test and post-test with non-equivalent control group was applied in this study. Twenty-six nurses were selected using purposive sampling technique. The intervention group received a combination bath, a sauna, and aromatherapy eucalyptus for 15 minutes and restful sleep at night for 8 hours. Whereas group control only rested at night for 8 hours. Result: The results showed a significant different among intervention on fatigue (p=0. 000) and lactic acid (p=0. 000). The Cohen score of calculation of the results calculates the total sample and mean±sd in the intervention group. The control group used an effect size calculator for the t-test. Variable fatigue values were obtained, with the value of Cohen's d effect in the medium effect size category, namely 0. 32. Whereas, variable lactic acid got a score of Cohen's d effect 0. 74, which shows the impact which sizes strong. Conclusion: The conclusion confirmed that combination between sauna bathing and eucalyptus aromatherapy could effect the fatigue and acid-level lactate among nurses with covid-19. Recommendation: Nursing interventions of combining between sauna bathing and eucalyptus aromatherapy could be used as a complementary therapy that could be applied at health centers or other health services to overcome fatigue and decrease lactic acid levels in coronavirus disease (covid-19). Further research need to add the duration of intervention to test the effectiveness of intervention on reducing fatigue and levels of lactic acid